Moderating roles of digital competence on accounting information system and employee productivity in the Nigerian manufacturing industry - Ighoroje, James Ese; Onojaife, Caroline Azuoma; Sinebe, Tonbraladoh Michael; Onuorah, Anastasia Chi-Chi; Onyeogo, Solomon (International Journal of Innovative Research and Scientific Studies, 2025)
This research aimed at examining the moderating roles of digital competence on the relationship between Accounting Information Systems (AIS) measured by information quality (IFQ), data quality (DAQ), service quality (SEQ), system quality (SYQ), and employee productivity (EMP). Out of the 500 copies of the questionnaire distributed to the management staff of the sampled manufacturing firms in South-South, Nigeria, 481 questionnaires were returned. The questionnaire items were coded using a 5-point Likert scale. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the sourced data. Although the AIS success factors (IFQ, DAQ, SEQ, and SYQ) improve EMP, digital competence (DIC) further enhances the AIS-EMP relationship, suggesting that employees perform better when they have access to high-quality information, reliable service support, accurate data, and well-functioning systems. Employees who work in highly digitally inclusive environments experience greater productivity gained from high information quality, service excellence, data integrity, and system reliability. The study underscores that if firms invest in improving their employees’ digital skills through technology-driven training, employees will become more productive. Additionally, Nigerian manufacturing firms should enhance their service delivery, maintain a strong database, and ensure robust system functionality should they desire to improve their employee productivity.